2022
DOI: 10.1002/art.41992
|View full text |Cite
|
Sign up to set email alerts
|

VEXAS Syndrome: A Case Series From a Single‐Center Cohort of Italian Patients With Vasculitis

Abstract: Objective To identify patients with VEXAS syndrome (vacuoles, E1 enzyme, X‐linked, autoinflammatory, somatic syndrome) from a single‐center cohort of Italian patients with vasculitis, using a clinically oriented phenotype‐first approach. Methods We retrospectively reviewed the clinical records of 147 consecutive male patients followed up in our vasculitis clinic from 2013 to date. All patients with a diagnosis of vasculitis and treatment‐resistant manifestations of inflammation, persistently elevated inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 10 publications
2
50
0
3
Order By: Relevance
“…In addition, functional studies of aberrant neutrophils [1] showed enhanced spontaneous neutrophil extracellular trap (NET) formation which can lead to endotheliitis, and platelet activation and aggregation. Evidence of cutaneous, pulmonary and systemic vasculitis [1,4,5] as well as ANCA-associated vasculitis [19] reflects multisystem autoinflammation. The presence of pathological antiphospholipid antibodies could enhance thrombogenesis by upregulation of tissue factor production and complement activation, leading to the activation of platelets and monocytes as well as promotion of the coagulation cascade [20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, functional studies of aberrant neutrophils [1] showed enhanced spontaneous neutrophil extracellular trap (NET) formation which can lead to endotheliitis, and platelet activation and aggregation. Evidence of cutaneous, pulmonary and systemic vasculitis [1,4,5] as well as ANCA-associated vasculitis [19] reflects multisystem autoinflammation. The presence of pathological antiphospholipid antibodies could enhance thrombogenesis by upregulation of tissue factor production and complement activation, leading to the activation of platelets and monocytes as well as promotion of the coagulation cascade [20].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of autoimmune biomarkers has not been systematically reported in previous reports of VEXAS patients; however, there has been reports of ANCA-positive patients with VEXAS as well as patients with antiphospholipid antibodies. 8 Thus, the lack of autoantibodies in the present case series, should not lead to premature conclusions of negative autoimmune biomarkers in VEXAS.…”
Section: Discussionmentioning
confidence: 68%
“…Darüber hinaus wurde auch das Vorkommen bei einer Vielzahl von Vaskulitiden, darunter ANCA-assoziierte Vaskulitis 9 , Behçet-Syndrom 10 , Polyarteriitis nodosa oder Großgefäßvaskulitis berichtet 4 .…”
Section: Klinisches Bildunclassified